Implementación de un sistema de producción mas limpia en la Universidad Nacional de Chimborazo, Campus Edison Riera. - Burbano, Diego, Domínguez Huilca, Luis Felipe (2016)
This project describes the Cleaner Production techniques applicable to the National University of Chimborazo, North Campus "Ms. Riera Edison ". The main objective of the project is to develop a Handbook for Implementing a System of Cleaner Production, theoretical support of several authors was obtained to explain the creation of the basis of the program, diagnosis, procedure, techniques and daily and monthly consumption results of water, energy and solid waste resources. For the preparation of the proposed Manual System Cleaner Production use of good environmental practices for energy resource such as changing lighting, replacement of taps and sanitary toilets for water resource and separation was raised in the source of solid waste, which will reduce consumption of resources through technical studies and environmental feasibility. Thus it was determined that the Cleaner Production System served for the use of resources based on the results of power consumption of 131,681 kW / month, you can get a difference of 18,840.6 kW / month savings; the total water consumption of the Campus is mᶟ 19,724.66 / year, with the implementation of automatic faucets and sanitary water consumption decrease mᶟ 1055.91 / year; the generation of solid waste is 923.39 kg / month intends to implement a separation of solid waste at the source. By statistical Chi-Square test it showed that the system is optimal because the hypothesis is accepted.